2016
DOI: 10.3389/fmicb.2016.01741
|View full text |Cite
|
Sign up to set email alerts
|

Livestock-Associated Methicillin Resistant Staphylococcus aureus (LA-MRSA) Clonal Complex (CC) 398 Isolated from UK Animals belong to European Lineages

Abstract: In recent years, there has been an increase in the number of livestock-associated methicillin resistant Staphylococcus aureus (LA-MRSA) clonal complex (CC) 398 recovered from S. aureus isolated animals in the UK. To determine possible origins of 12 LA-MRSA CC398 isolates collected after screening more than a thousand S. aureus animal isolates from the UK between 2013 and 2015, whole genome sequences (WGS) of CC398 European, including UK, and non-European isolates from diverse animal hosts were compared. Phylog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 34 publications
4
53
2
Order By: Relevance
“…Phylogenetic analysis using cgMLST of all published, sequenced CC398 LA‐MRSA from the United Kingdom shows a diverse population which others have shown are related to mainland European isolates and is consistent with multiple introductions into the United Kingdom (Ward et al ; Sharma et al ). This current analysis is the largest collection of sequenced LA‐MRSA CC398 from the United Kingdom and indicates the close genetic linkage between a pair of human and turkey isolates which were both isolated in the east of England in 2013 and which are separated by 12 genome SNPs.…”
Section: Discussionsupporting
confidence: 53%
“…Phylogenetic analysis using cgMLST of all published, sequenced CC398 LA‐MRSA from the United Kingdom shows a diverse population which others have shown are related to mainland European isolates and is consistent with multiple introductions into the United Kingdom (Ward et al ; Sharma et al ). This current analysis is the largest collection of sequenced LA‐MRSA CC398 from the United Kingdom and indicates the close genetic linkage between a pair of human and turkey isolates which were both isolated in the east of England in 2013 and which are separated by 12 genome SNPs.…”
Section: Discussionsupporting
confidence: 53%
“…In European countries and in North America, CC398 was the overwhelmingly dominant LA MRSA, whereas CC9 predominated in most Asian countries (Cortimiglia et al, 2016; Sharma et al, 2016). In our study, all CC398 strains were identified as MSSA strains.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we sought to detect the presence of sip, an integrase carried by the Staphylococcal pathogenicity island (SaPI) that usually carries bap. 22 Finally, a panel of the most common antimicrobial resistance genes found in the United Kingdom MRSA CC398 23 was also included for screening (ermA, ermB, ermC, tetK, tetM, aacA-aphD, fexA, cfr, and dfrK). [24][25][26][27][28] Positive and negative controls for PCR reactions were included in each assay.…”
mentioning
confidence: 99%